DRASTIC: Geographic Information System Model for Evaluating Groundwater Pollution Potential - มาจันแดง จิระเดช (KKU Science Journal, 2013)
DRASTIC is the most widely used method for evaluating groundwater pollution potential. This method is the geographic information system model in the form of index model and use the overlay method for data analysis. DRASTIC are acronym of words in English, include: Depth to water, [net] Recharge, Aquifer media, Soil media, Topography [slope], Impact of vadose zone, and Conductivity [hydraulic] of the aquifer. The result index is ranged for classifying the groundwater pollution potential levels. DRASTIC model validation effort is always constrained by the quantity and quality of the factors, in particular the factors have high influence in the model.